THE EFFECTS OF IS RESOURCES ON AIS CAPABILITIES AND PERFORMANCE OF MALAYSIAN CO-OPERATIVES - Mohd Hadzrami Harun Rasit (International Journal of Accounting, Finance and Business, 2021)
Accounting information systems (AIS) capabilities are essential because of their ability to process business data into useful and timely information according to users’ requirements. Indeed, empirical evidences suggested that the use of AIS has positive impact on firm performance. However, factors that contribute to AIS capabilities and consequently improve co-operative’s performance were not adequately explained. As such, this paper draws on the resource-based view (RBV) to examine the factors that influence AIS capabilities and performance of Malaysian co-operatives. Using a quantitative approach, questionnaires are used to collect data from 115 co-operative managers across Malaysia. Partial Least Square- Structural Equation Modelling is used to analyse the data. The study found that IS technical skills, and planning and change management are significant factors that influence AIS capabilities. Theoretically, the study contributes to knowledge by providing an understanding of the roles of IS resources in AIS capabilities building. Also, the study provides support for the importance of IS resources in AIS capabilities building and improving performance. Practically, the study provides guidelines for co-operatives’ stakeholders, particularly management, in planning and managing their IS resources.